A nova ciência de Giambattista Vico e os princípios norteadores do nascimento e desenvolvimento do mundo civil - Oliveira, Rosana Rodrigues de (2020)
This dissertation seeks to outline Giambattista Vico’s thought (1668 – 1744) regarding the universal principles of the common nature of nations, the way human customs and history determine the establishment and development of the world of nations. In Vico’s scheme of necessary evolution of every culture, three periods are well distinguished: age of gods, age of heroes and age of men. At the ages Vico articulates three basic principles in all nations, regardless of whether they know or relate to each other: religion, marriage and the burial of the dead. Customs that are part of the human race as a historical process. The themes of historical courses and recurrences are also Vichian New Science topics. According to Vico one can only know what one does. Man does not know the essence of nature, because he is not the creator of the universe. However, man creates history, and so can know it. The philosopher realized the importance of the historical man, affirming that through the study of the philology and the philosophy one can reach the knowledge of the life of the oldest peoples, the fables, the poets, until the formation of the civil world. Highlighting the maxim verum et factum convertuntur (I know because I do, I do because I know). The history of humanity was effectively the history of reason, fantasy, sensitivity, imagination that together and articulated place man as the subject and object of history, that is, man has the ability to gather and interpret events to from universal principles that repeat themselves and take their own contours in each age cycle that makes up the history of men. In it, men in making history suffer their deeds. Thus the New Science investigates the laws, customs, language, thought development, constants, and regularities of the common nature of nations. Based on this, divine providence is the logic of the events present in humanization and human barbarism. Providence is the lawgiver and leaves man (the craftsman) the burden of understanding the meaning and ends of his own actions. It’s responsible for guiding and ordering the historical facts. Providence shows itself in historical events, so that for Vico the historical-civil world was not formed spontaneously, by chance, but rather led by men and ordained by providence. Providence humanizes that ferocious man seen since the age of the gods and who has evolved over time. That is, it is the astonishing human overcoming endowed with a divine mind that thinks and makes history, that converts ferocious passions into virtues, isolation into social conduct.